2016
DOI: 10.1111/cmi.12628
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis late blight: infection of a nonhost plant byAlbugo laibachiienables full colonization byPhytophthora infestans

Abstract: SummaryThe oomycete pathogen Phytophthora infestans causes potato late blight, and as a potato and tomato specialist pathogen, is seemingly poorly adapted to infect plants outside the Solanaceae. Here, we report the unexpected finding that P. infestans can infect Arabidopsis thaliana when another oomycete pathogen, Albugo laibachii, has colonized the host plant. The behaviour and speed of P. infestans infection in Arabidopsis pre‐infected with A. laibachii resemble P. infestans infection of susceptible potato … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 83 publications
(185 reference statements)
0
13
0
Order By: Relevance
“…Studies on other pathogens have documented Table S2 shows that pathogen genotypes derived from these by recombination are also all virulent on at most one host species. priority effects, in which, for example, inoculation by a virulent pathogen facilitates infection in a subsequent inoculation by a normally avirulent pathogen (41)(42)(43). However, when a virulent and an avirulent pathogen are simultaneously inoculated, such priority effects are generally absent (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other pathogens have documented Table S2 shows that pathogen genotypes derived from these by recombination are also all virulent on at most one host species. priority effects, in which, for example, inoculation by a virulent pathogen facilitates infection in a subsequent inoculation by a normally avirulent pathogen (41)(42)(43). However, when a virulent and an avirulent pathogen are simultaneously inoculated, such priority effects are generally absent (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that A. laibachii Nc14 (AlNc14) [47] suppresses Arabidopsis NHR to P. infestans ([12], Fig. 1a, b, d and e).…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis ( Arabidopsis thaliana ) plants were grown as previously described [12]. Seeds were sown on Scotts Levington F2 compost (Scotts, Ipswich, UK) and vernalized for one week at 5–6 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations